Quorum Sensing: Cell to Cell Signaling mechanism - Sharma, Neelima; Mohapatra, Animesh Kumar (SCHOOL SCIENCE, 2015)
Communication is considered as the strongest and most important property ever evolved by nature for every living creation. It takes place by cell-to-cell signaling process which is prerequisite for development of multicellular organisms such as animals and plants but has also evolved in groups which are not usually described as multicellular, i.e., bacteria and unicellular fungi. It is perhaps an important tool in battle for survival. One of the mechanisms for bacterial cell-to-cell signaling and behaviour coordination under changing environments is referred to as quorum sensing. Quorum sensing was first observed in Vibrio fischeri, a bioluminescent bacterium that lives as a mutualistic symbiont in protophore (or light producing organ) of the Hawaiian bobtail squid. In case of free living Vibrio fischeri, autoinducer (small signaling molecule) is at low concentration and thus cells do not luminance. But when they are highly concentrated in the protophore (about 1011 cells/ml) transcription of luciferase is induced, leading to prominent bioluminescence.